Gel electrolyte, preparation method and solid-state lithium battery

By developing new liquid initiator and cycloether-based monomer in situ polymerization technology, gel electrolytes with excellent low-temperature performance were prepared, which solved the problem of performance degradation of gel electrolytes under low temperature conditions in the prior art, and achieved high-performance solid-state lithium battery application in low-temperature environments.

CN119833746AActive Publication Date: 2025-04-15NANKAI UNIV

Patent Information

Application Number
CN202510154288.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-15
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The existing gel electrolytes have slow ion kinetics under low temperature conditions, lower conductivity, lower interface charge transfer rate, and organic liquid phase components may solidify, making it difficult to meet the application needs of low-temperature environments.

Method used

By developing new liquid initiators, gel electrolytes are prepared by in-situ polymerization of cycloether-based monomers, the amount of liquid phase components is reduced and the low-temperature performance is improved.

Benefits of technology

Under low temperature conditions, the ionic conductivity of the gel electrolyte remains high, avoiding the solidification of liquid phase components, significantly improving the low-temperature performance, reducing the amount of liquid phase components, reducing the loss of energy density and safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833746A_ABST
    Figure CN119833746A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials and devices, and relates to a gel electrolyte, a preparation method and a solid-state lithium battery, a liquid novel initiator with a low freezing point, a cyclic ether polymeric monomer and a plasticizer are mixed to form a homogeneous precursor solution, the precursor solution is injected into a battery shell, standing is performed at normal temperature (20-35 DEG C) for in-situ polymerization, and the solid-state lithium battery is obtained. And the gel electrolyte-based solid-state battery can be obtained. The gel electrolyte is initiated by a novel initiator, and compared with a common initiator, the gel electrolyte has better low-temperature performance, and a high-performance solid-state lithium battery is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials and devices, and in particular to a gel electrolyte, a preparation method, and a solid-state lithium battery. Background Art

[0002] Most of the liquid electrolytes currently used on a large scale have the risk of leakage and flammability. Therefore, the development of high-safety lithium batteries with solid and quasi-solid electrolytes as the core is a necessary means to upgrade the battery system.

[0003] Gel electrolytes are composed of a polymer matrix and a liquid plasticizer, combining the advantages of all-solid-state electrolytes and liquid electrolytes. In gel polymer electrolytes, the polymer matrix provides a certain mechanical strength and flexibility, while the liquid phase component can improve the ionic conductivity and interface stability. The polymer skeleton locks the organic liquid phase component, making the electrolyte as a whole a non-flowing gel state, avoiding the risk of leakage of the liquid electrolyte. It is the most promising solid electrolyte at this stage. In-situ polymerization can make the solid electrolyte have good contact with both the positive and negative electrodes and form an ion path to match the high-load positive electrode. It is a very promising method for preparing gel electrolytes.

[0004] However, although the ionic conductivity of many gel polymer electrolyte films can reach a level close to that of liquid electrolytes at room temperature (10 -3 S cm -1 ), but under low temperature conditions, Li + The kinetics are slow, the ionic conductivity of the gel polymer electrolyte drops significantly, the interfacial charge transfer rate decreases, and the organic liquid phase components are also likely to solidify, making it difficult to meet the actual application requirements in low-temperature environments.

[0005] Therefore, it is particularly important to improve the low-temperature performance of gel electrolytes by various means.

[0006] There are two common methods to improve the low-temperature performance of gel electrolytes. One is to improve the contact between the electrode and electrolyte interfaces by in-situ polymerization, accelerate the transfer rate of interfacial charge, and avoid low-temperature solidification of organic electrolyte components, thereby ensuring the rapid transport of ions between liquid phase molecules at low temperatures; the other is to select an organic solvent with a lower freezing point as a plasticizer component. Researchers often combine these two methods to achieve better low-temperature performance. At present, most experts and scholars at home and abroad choose to regulate the plasticizer component for research. However, in order to achieve ideal low-temperature performance, the system needs to add an excess of liquid plasticizer (often using a plasticizer that exceeds the amount of polymerized monomers). For example, a liquid plasticizer with a 150% amount of cyclic ether monomer (DOL) is added to achieve excellent low-temperature performance at -20°C (Ciucci et al., Advanced Energy Materials, 2022, 12, 2102.). Such excessive liquid plasticizer usage will inevitably cause a loss of energy density, and may also cause a higher risk of leakage and certain safety hazards. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a gel electrolyte, a preparation method, and a solid-state lithium battery. A gel electrolyte with good low-temperature performance is prepared for assembling a high-performance solid-state lithium battery.

[0008] The technical solution for implementing the present invention is as follows:

[0009] The first aspect of the present invention provides a gel electrolyte, which is composed of a polymerization monomer solution, an initiator and a plasticizer in a volume ratio of 50-300:5-100:0-100.

[0010] The polymerizable monomer has a cyclic ether structure, the polymerizable monomer solution is obtained by adding lithium salt to the polymerizable monomer, and the initiator is methyl fluorosulfonyl difluoroacetate (MDFSA).

[0011] The polymerization monomer is one or more of 1,3-dioxolane (DOL), 1,3,5-trioxane (TXE), ethylene oxide, propylene oxide, butoxide, and tetrahydrofuran (THF); the lithium salt in the polymerization monomer solution is one or more of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB), lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), and lithium perchlorate (LiClO4), and the concentration of the lithium salt is 0.1 to 10 mol / L.

[0012] The present invention uses a novel initiator to initiate in-situ polymerization of cyclic ether-based monomers to prepare a gel electrolyte, which has good low-temperature performance.

[0013] Furthermore, the polymerization monomer solution, the initiator and the plasticizer are composed in a volume ratio of 100:10 to 50:30 to 70.

[0014] Preferably, the polymerization monomer solution, the initiator and the plasticizer are composed in a volume ratio of 100:30:30-70.

[0015] Furthermore, the plasticizer composition includes lithium salt and organic solvent, which can be mixed with the polymerizable monomer to form a uniform solution.

[0016] Furthermore, the plasticizer is obtained by adding lithium bistrifluoromethanesulfonyl imide (LiTFSI) to fluoroethylene carbonate (FEC), and the concentration of lithium bistrifluoromethanesulfonyl imide is 0.5-3 mol / L.

[0017] The second aspect of the present invention provides a method of mixing and dissolving a cyclic ether-based polymerization monomer, an initiator, and a plasticizer to form a homogeneous precursor solution; and allowing the precursor solution to stand at 20° C.-35° C. for 3 h-48 h for in-situ polymerization.

[0018] A third aspect of the present invention is to provide a solid-state lithium battery comprising the above-mentioned gel electrolyte.

[0019] Furthermore, the positive electrode of the solid-state lithium battery is any one of lithium-rich manganese-based, nickel-cobalt-manganese-based, lithium cobalt oxide, and lithium iron phosphate, and the negative electrode is any one of lithium metal, lithium-based alloy, silicon carbon, and graphite.

[0020] Furthermore, the shell of the solid-state lithium battery is one of a soft-pack battery, a square battery, a cylindrical battery, a stacked battery, and a wound battery.

[0021] Preferably, the battery housing includes but is not limited to a commercial XR2032 assembled battery, and the amount of the electrolyte precursor solution is 10 μL-100 μL.

[0022] Advantages and beneficial effects of the present invention:

[0023] 1. The present invention develops a liquid phase initiator with low temperature performance. When the liquid phase component of the system is only 80% of the cyclic ether monomer (DOL), it also achieves excellent low temperature performance at -20°C, greatly reducing the amount of liquid phase components in the gel electrolyte.

[0024] 2. The present invention develops a new type of liquid initiator with a low freezing point to initiate the ring-opening polymerization of cyclic ether-based polymerization monomers. When other conditions such as the plasticizer are the same, it has better low-temperature performance than commonly used initiators. It is a very potential preparation method for low-temperature solid-state battery gel electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1is an optical picture of the gel electrolyte after polymerization in Example 1;

[0026] Figure 2 It is the infrared (FT-IR) spectrum test diagram of the gel electrolyte after polymerization in Example 1 and the comparative samples DOL+1M LiTFSI and FEC / 1M LiTFSI;

[0027] Figure 3 It is a Raman spectrum test chart of the gel electrolyte after polymerization in Example 1 and the comparative samples DOL+1M LiTFSI and FEC / 1M LiTFSI;

[0028] Figure 4 is the ionic conductivity at different temperatures of the SS-SS half-cell test assembled in Example 1;

[0029] Figure 5 This is the charge and discharge curve of the third cycle at room temperature and -20°C in Example 2;

[0030] Figure 6 This is the charge and discharge curve of the third cycle at room temperature and -20°C in comparative example 1;

[0031] Figure 7 It is a graph showing the capacity variation with cycles of Example 2 (blue) and Comparative Example 1 (red) at -20°C. DETAILED DESCRIPTION

[0032] The present invention will be further explained below through the accompanying drawings and specific examples. The following examples are only used as an illustration and should not be understood as limiting the scope of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0033] Example 1

[0034] First, 1M LiTFSI was dissolved in the polymerization monomer (DOL), and then 100 μL of the solution was taken out and mixed with 30 μL MDFSA (new initiator) and 50 μL FEC / 1M LiTFSI (plasticizer) to form a homogeneous precursor solution;

[0035] The precursor solution in the vial was left to stand at room temperature (20°C-35°C) until the in-situ polymerization was completed, and the optical image of the gel electrolyte was obtained. At the same time, infrared (FT-IR) spectroscopy and Raman (Raman) spectroscopy tests were performed with the comparative sample polymerization monomer DOL+1M LiTFSI and plasticizer FEC / 1M LiTFSI.

[0036] The precursor solution that was not left to stand in Example 1 was assembled into a half-cell, and the SS-SS half-cell was assembled with stainless steel gaskets (SS) as the positive and negative electrodes. The amount of precursor solution was 50 μL, and the battery was assembled using 0.85 tons of pressure and then left to stand at room temperature (20°C-35°C) for 24 hours to complete the in-situ polymerization. The diaphragm was Celgard 2500, and the injection tool was a pipette with a range of 100 μL.

[0037] Figure 1 The graph shows the polymerization of the precursor solution in the vial of Example 1 after standing at room temperature for 24 hours. The flowing liquid in the vial turns into a gel state and cannot flow, indicating that the polymerization reaction is completed. Figure 2 The infrared (FT-IR) spectra of Example 1 and the comparative sample (polymerized monomer, plasticizer) are shown in Figure 1. The monomer is at ~915 cm -1 The characteristic peak at 848 cm -1 The appearance of long chain peaks indicated the completion of the polymerization reaction. Figure 3 The Raman spectra of Example 1 and the comparative sample (polymerized monomer, plasticizer) are shown in Figure 1. The monomer has a peak at ~937 cm -1 The COC characteristic peak disappears at 845 cm -1 The appearance of characteristic peaks also indicates the completion of the polymerization reaction. Figure 4 The ionic conductivity test results of the SS-SS half-cell at different temperatures after the SS-SS half-cell in Example 1 was left at room temperature for 24 hours. The ionic conductivity of the gel electrolyte was still ~0.1 mS / cm at -20°C, which shows that it has the potential for low-temperature operation.

[0038] Example 2

[0039] First, 1M LiTFSI was dissolved in the polymerization monomer (DOL), and then 100 μL of the solution was taken out and mixed with 30 μL MDFSA (new initiator) and 50 μL FEC / 1M LiTFSI (plasticizer) to form a homogeneous precursor solution;

[0040] The precursor solution that was not left to stand in Example 2 was assembled into a battery. The battery shell was a commercial XR2032 assembled battery. The positive electrode was lithium iron phosphate, the negative electrode was lithium metal, and the positive electrode diameter of the full battery was 10 mm and the loading was 2 mg cm -2 The negative electrode is a Li sheet with a diameter of 14 mm and a thickness of 450 μm. The amount of precursor solution added is 50 μL. The battery is assembled using a 0.85-ton pressure and then left to stand at room temperature (20°C-35°C) for 24 hours to complete in-situ polymerization. The diaphragm is Celgard 2500, and the injection tool is preferably a pipette with a range of 100 μL.

[0041] The assembled half-cell was activated at room temperature at 0.1C, 2.5-4.0V for 3 cycles, and then charged and discharged at -20℃ at 0.1C, 2.5-4.0V. 1C = 170mAh g -1 . Figure 5 The charge-discharge curve of the third cycle at room temperature and -20°C in Example 2. The discharge capacity of the third cycle at room temperature is 161.3 mAh g -1 , the discharge capacity of the third cycle at -20℃ is 87.1mAh g -1 , which is 54.0% of the normal temperature capacity.

[0042] Comparative Example 1

[0043] A method for preparing a cyclic ether-based gel electrolyte using a common initiator: first dissolving 1M LiTFSI in a polymerized monomer (DOL), then taking out 100 μL of the solution and mixing and dissolving it with 80 μL FEC / 1M LiDFOB (plasticizer, LiDFOB can also be used as an initiator) to form a homogeneous precursor solution;

[0044] The battery was assembled using the precursor solution that was not left to stand in Comparative Example 1. The battery shell was a commercial XR2032 assembled battery. The positive electrode was lithium iron phosphate and the negative electrode was lithium metal. The positive electrode diameter of the full battery was 10 mm and the loading was ~2 mg cm -2 The negative electrode is a Li sheet with a diameter of 14 mm and a thickness of 450 μm. The amount of precursor solution added is 50 μL. The battery is assembled using a 0.85-ton pressure and then left to stand at room temperature (20°C-35°C) for 24 hours until in-situ polymerization is completed. The diaphragm is Celgard 2500, and the injection tool is preferably a pipette with a range of 100 μL.

[0045] The assembled half-cell was activated at room temperature at 0.1C, 2.5-4.0V for 3 cycles, and then charged and discharged at -20℃ at 0.1C, 2.5-4.0V. 1C = 170mAh g -1 . Figure 6 This is the charge and discharge curve of the third cycle of comparative example 1 at room temperature and -20°C. The discharge capacity of the third cycle at room temperature is 156.7 mAh g -1 , the discharge capacity of the third cycle at -20℃ is 71.0mAh g -1 , which is only 45.3% of the capacity at room temperature.

[0046] Figure 7 The cycle-capacity change diagram of Example 2 and Comparative Example 1 at -20°C shows that the capacity retention ability of Example 2 at low temperature (100-cycle capacity retention rate is 93.3%) is significantly higher than that of Comparative Example 1 (100-cycle capacity retention rate is 63.2%).

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and optimizations can be made, including improvements and optimizations to polymer monomers with cyclic ether groups, plasticizers, lithium salts, and new liquid initiators with low freezing points. These improvements and optimizations should also be regarded as the scope of protection of the present invention.

Claims

1. A gel electrolyte, characterized in that: It is composed of a polymerization monomer solution, an initiator and a plasticizer in a volume ratio of 50-300:5-100:0-100; The polymerizable monomer has a cyclic ether structure, and the polymerizable monomer solution is obtained by adding lithium salt to the polymerizable monomer; The initiator is methyl fluorosulfonyl difluoroacetate.

2. The gel electrolyte according to claim 1, characterized in that The polymerization monomer is one or more of 1,3-dioxolane, 1,3,5-trioxane, ethylene oxide, propylene oxide, butoxide, and tetrahydrofuran; the lithium salt in the polymerization monomer solution is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium perchlorate, and the concentration of the lithium salt is 0.1 to 10 mol / L.

3. The gel electrolyte according to claim 1, characterized in that The plasticizer is composed of a lithium salt and an organic solvent, wherein the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium perchlorate, and the organic solvent is one or more of fluoroethylene carbonate, dimethyl carbonate, 1,2-dimethoxyethane, and methyl propionate.

4. The gel electrolyte according to claim 3, characterized in that: The plasticizer is obtained by adding lithium bistrifluoromethanesulfonyl imide to fluoroethylene carbonate, and the concentration of lithium bistrifluoromethanesulfonyl imide is 0.5-3 mol / L.

5. The method for preparing the gel electrolyte according to any one of claims 1 to 4, characterized in that: The cyclic ether-based polymerization monomer, initiator and plasticizer are mixed and dissolved to form a homogeneous precursor solution; the precursor solution is allowed to stand at 20° C.-35° C. for 3 h-48 h for in-situ polymerization.

6. A solid-state lithium battery comprising the gel electrolyte according to any one of claims 1 to 4.

7. The solid-state lithium battery according to claim 6, characterized in that: The positive electrode of the solid-state lithium battery is any one of lithium-rich manganese-based, nickel-cobalt-manganese-based, lithium cobalt oxide, and lithium iron phosphate, and the negative electrode is any one of lithium metal, lithium-based alloy, silicon carbon, and graphite.

8. The solid-state lithium battery according to claim 6, characterized in that: The shell of the solid-state lithium battery is one of a soft-pack battery, a square battery, a cylindrical battery, a laminated battery, and a wound battery.

Citation Information

Patent Citations

  • Flame-retardant additive for electrolyte and flame-retardant lithium ion battery electrolyte

    CN103633368A

  • High-rate fiber lithium ion battery

    CN115133105A

  • Gel polymer electrolyte for low-temperature operation, solid-state battery and preparation method of solid-state battery

    CN116487689A

  • electrolyte

    JP2012216361A

  • Nonaqueous electrolyte solution for power storage device

    JP2017168347A

Cited By

  • Ether-based solid polymer electrolyte, preparation method thereof and application of ether-based solid polymer electrolyte in sodium secondary battery

    CN121215883A

  • An ether-based solid-state polymer electrolyte, a preparation method thereof, and application thereof in a sodium secondary battery

    CN121215883B

  • Ultrahigh-energy-density solid-state lithium metal battery and preparation method thereof

    CN121618064A